EURASIP Journal on Audio, Speech, and Music Processing - Habets, Emanuël A.P
The aim of EURASIP Journal on Audio, Speech, and Music Processing is to bring together researchers, scientists and engineers working on the theory and applications of the processing of various audio signals, with a specific focus on speech and music. EURASIP Journal on Audio, Speech, and Music Processing will be an interdisciplinary journal for the dissemination of all basic and applied aspects of speech communication and audio processes. Its primary objectives are: To publish articles on the advancement of both human speech communication science and automatic speech and audio systems To allow rapid and wide diffusion of excellent contributions in these areas To provide world-wide, barrier-free access to the full text of research articles To conduct a rapid but thorough review process in order to assure high quality articles To provide immediate web access once an article is editorially approved The journal will be dedicated to having original research work, but will also allow tutorial and review articles. Articles will deal with both theoretical and practical aspects of audio, speech, and music processing. The journal is an Open Access journal since 2006.